Image Scrambling Using One Time Pad with Linear Congruent Key Generator - Imam Saputra (STMIK Budi Darma, 2017)
With the changing of the times, more and more moments can be photographed. Digital imagery stores a lot of information through visual display. Many people perpetuate the things that are personal in the form of digital imagery, with so many files in the form of digital imagery that is private and not for publication. With the development of cloud computing systems, every image recorded through the smartphone will be synchronized with the online storage service provider. This has many advantages, such as users do not have to worry about the damage to storage devices that exist in their gadgets. But the disadvantage of this system is that if an account falls into the hands of an unauthorized person then photographs containing this personal information may be published by an unauthorized person, of course this will be very detrimental. One solution that can be used is to randomize the original image so that its visual appearance will not be like the actual visual display. One way that can be used for image randomization is by cryptographic techniques. The one time pad algorithm is a very powerful classical cryptographic algorithm and can not be solved by cryptanalis until now. One disadvantage of a one time pad algorithm is the key length must be the same as the length of the plaintext. This makes the algorithm unused because it is less practical in its key usage. To overcome this required a key generator that could generate randomly generated locks ie a linear congruent generator, thus the key length must be equal to the length of the plaintext can be generated only with a few variables. In this way, image randomization can be done with a strong and practical cryptographic algorithm.